A comparative study on the performance and emissions from a CI engine fuelled with water emulsified diesel prepared by mechanical homogenization and ultrasonic dispersion method - Pijush Kanti Mondal; Bijan Kumar Mandal (Energy Reports, 2019)
In this study, the authors have tried to compare the stability behaviour of water emulsified diesel (WED) prepared by mechanical homogenizer and ultrasonicator. Both types of emulsion have been prepared by adding 10% water and 2% surfactant mixture of Span 80 and Tween 80. The emulsion prepared by ultrasonicator (WED U) shows higher stability than that prepared by mechanical homogenizer (WEDM). Two important physical properties namely, viscosity and density of the prepared WEDs have been measured and compared to those with base diesel. Experimental investigations have also been carried out in a diesel engine using neat diesel as well as WEDs to compare the effect of mechanical homogenization and ultrasonication methods on combustion, performance and emission characteristics of the engine. The emulsion prepared using ultrasonicator shows improved combustion characteristics due to smaller size and more homogeneous distribution of the water particles. Higher brake thermal efficiency and lower brake specific fuel consumption are observed using WEDU. Both the combustion and the performance behaviours of the engine using emulsions prepared by ultrasonicator show improved characteristics. But, the results are not much encouraging of WEDM. NOx and smoke emissions are noted to be significantly reduced for both types of prepared emulsions. However, the difference in CO emission at full load condition is found to be marginal.
Keywords: 330; Combustion characteristics; Emission characteristics; Emulsion stability; Mechanical homogenization; Ultrasonication